Pengaruh Label “Tasya Farasya Approved” dan Konten Medsos Marketing Tiktok terhadap Keputusan Pembelian Hanasui Glazedorable Vinyl Stain - Pirous, Haekal (Ma'soem University, 2025)
This study aims to examine the impact of the “Tasya Farasya Approved” label and TikTok-based social media marketing content on consumer purchasing decisions for Hanasui Glazedorable Vinyl Stain. The research adopted an associative quantitative approach involving 100 respondents selected through purposive sampling, specifically TikTok users who follow Tasya Farasya and the official Hanasui account. Data were collected using online questionnaires and processed with SPSS version 23 through validity, reliability, and normality testing, as well as multiple correlation, regression analysis, coefficient of determination, and hypothesis testing using t-test and F-test. The findings reveal that the “Tasya Farasya Approved” label has a significant effect on purchasing decisions, contributing 38.0%, while TikTok marketing content contributes 28.8%. Simultaneously, both variables explain 45.2% of the variance in purchasing decisions. These results indicate that influencer endorsement combined with engaging social media marketing content plays an important role in shaping consumer buying behavior.